2001
DOI: 10.1002/1521-396x(200111)188:1<101::aid-pssa101>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Device Properties in AlGaInN-Based Laser Diodes by Time-Resolved Photoluminescence

Abstract: We estimated the optical characteristics of AlGaInN-based laser structures by time-resolved and standard photoluminescence. It was clarified that the microscopic distribution of the peak wavelength of GaInN active layers has a strong correlation with the threshold current and the slope efficiency. As an index representing the extent of this distribution, we used the depth in the tail states of the active layer, E 0 , for which we found an excellent correlation with the device properties. From an estimation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…A wavelength dependency of the carrier lifetime frequently observed in those experiments is usually explained by carrier localization. 20,21 From our experiments we would argue that stimulated emission is the reason for the wavelength dependent carrier lifetime.…”
Section: Contribution Of Stimulated Emission To Carrier Decaymentioning
confidence: 99%
“…A wavelength dependency of the carrier lifetime frequently observed in those experiments is usually explained by carrier localization. 20,21 From our experiments we would argue that stimulated emission is the reason for the wavelength dependent carrier lifetime.…”
Section: Contribution Of Stimulated Emission To Carrier Decaymentioning
confidence: 99%
“…One of the main challenges is to grow indium‐rich InGaN layers with good crystal quality 1. Homogeneous indium incorporation in the ternary InGaN QW layer is a key parameter to obtain highest peak gain and best laser results 2–4. Hence, it is necessary to gain a better understanding of InGaN growth mechanisms to optimize the QW growth to reach highest uniformity and lowest defect density.…”
Section: Introductionmentioning
confidence: 99%
“…Such fluctuations form nanometerscale potential minima in InGaN QWs and create carrier localization centers. Although carrier localization centers improve internal quantum efficiencies (IQEs) for blue lightemitting diodes (LEDs), 10,11) it has been reported that a large localization energy deteriorates the threshold current and slope efficiency of LDs 12) and drastically reduces the photoluminescence (PL) intensity with dark spots in InGaN QWs in the green region. 13,14) Recently, Enya et al have reported 531 nm green lasing under pulsed operation, 15) and Yoshizumi et al have reported cw operation at 520 nm on novel semi-polar f20 21g GaN substrates.…”
mentioning
confidence: 99%
“…Thus, the f20 21g plane appears suitable for green LDs with respect to the threshold current and slope efficiency. 12) Figure 3 shows (a) PL spectra and (b) the peak energy at 6 K as functions of excitation energy densities. The excitation energy densities were changed between 8.6 and 29,000 nJ/cm 2 , which correspond to a photogenerated carrier density from 1:7 Â 10 14 to 5:7 Â 10 17 cm À3 .…”
mentioning
confidence: 99%